2021
DOI: 10.1101/2021.02.02.21250799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infection and mRNA-1273 vaccine antibodies neutralize SARS-CoV-2 UK variant

Abstract: Antibody responses against the SARS-CoV-2 Spike protein correlate with protection against COVID-19. Serum neutralizing antibodies appear early after symptom onset following SARS-CoV-2 infection and can last for several months. Similarly, the messenger RNA vaccine, mRNA-1273, generates serum neutralizing antibodies that are detected through at least day 119. However, the recent emergence of the B.1.1.7 variant has raised significant concerns about the breadth of these neutralizing antibody responses. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 9 publications
2
52
0
3
Order By: Relevance
“…Studies addressing the effectiveness of the mRNA vaccines BNT162b2 (Pfizer–BioNTech; Mainz, Germany) and mRNA-1273 (Moderna; Cambridge, MA, USA) found that both infection-induced and vaccine-induced antibodies were effective in neutralising B.1.1.7. 34 , 35 , 36 The clinical efficacy of the ChAdOx1 vaccine (AstraZeneca; Cambridge, UK) against B.1.1.7 was found to be similar to the efficacy of the vaccine against other circulating lineages in the UK, according to a pre-print manuscript. 33 , 37 The ongoing clinical phase 3 trials of the protein-based vaccine NVX-CoV2373 (Novavax; Gaithersburg, MD, USA) reported 90% vaccine efficacy against the previous strains of SARS-CoV-2 and more than 85% efficacy against B.1.1.7.…”
Section: Discussionmentioning
confidence: 97%
“…Studies addressing the effectiveness of the mRNA vaccines BNT162b2 (Pfizer–BioNTech; Mainz, Germany) and mRNA-1273 (Moderna; Cambridge, MA, USA) found that both infection-induced and vaccine-induced antibodies were effective in neutralising B.1.1.7. 34 , 35 , 36 The clinical efficacy of the ChAdOx1 vaccine (AstraZeneca; Cambridge, UK) against B.1.1.7 was found to be similar to the efficacy of the vaccine against other circulating lineages in the UK, according to a pre-print manuscript. 33 , 37 The ongoing clinical phase 3 trials of the protein-based vaccine NVX-CoV2373 (Novavax; Gaithersburg, MD, USA) reported 90% vaccine efficacy against the previous strains of SARS-CoV-2 and more than 85% efficacy against B.1.1.7.…”
Section: Discussionmentioning
confidence: 97%
“…Within the the RBD, we and others have shown that the presence of N501Y mutation found in the B.1.1.7 UK variant does not affect the neutralizing ability of serum from either naturally infected or mRNA-1273 vaccinated individuals (Edara et al, 2021;Johnson et al, 2021;Rathnasinghe et al, 2021;Shen et al, 2021;Wu et al, 2021). The substitution at position E484, located in the receptor-binding ridge epitope (Greaney et al, 2021) (Johnson et al, 2021;Xie et al, 2021;Shen et al, 2021).…”
mentioning
confidence: 69%
“…It is postulated to enhance transmissibility of the virus by facilitating a conformational change in the S protein following protease activity at the cell membrane [15]. Previous serum neutralization assays for VSV-based SARS-CoV-2 pseudoviruses expressing the S protein with the P681H mutation demonstrated no significant changes in the titer required for neutralization compared to the unmutated S protein [28]. Additionally, no significant changes in the titer were needed for neutralization of the WT SARS-CoV-2 compared to a viral sample from the B.1.1.7 variant (in which P681H is one of its defining mutations), using sera from convalescent patients or individuals vaccinated with the Moderna mRNA-1273 vaccine from Moderna [28].…”
Section: Discussionmentioning
confidence: 99%